Students' Vocabulary Mastery and Their Reading Comprehension - fitria lisana; Gatot Subroto; Dewi Nopita (English Language Education Study Program Universitas Maritim Raja Ali Haji, 2022)
The purpose of this research was to find whether or not there is a relationship between vocabulary mastery and reading comprehension. The researcher focused on the relationship between students' vocabulary mastery and their reading comprehension in this study. The researcher employed a quantitative method in their investigation. The sample in this study was 30 students at seventh grade in SMPN 4 Senayang. 20 items for vocabulary mastery and 10 items for reading comprehension in a multiple-choice test were used to collect data for this study. The Pearson's Product Moment Correlation Coefficient was employed to analyze the data. The correlation coefficient variable of mastery of vocabulary and reading comprehension was 0.473 based on the data obtained by the authors. The correlation coefficient was 0.473, which is placed between 0.400.0.600 was seen in the table. The correlation is moderate correlation. As a result, Ho is rejected, while Ha is accepted. The authors found a relationship between students' vocabulary mastery and their reading comprehension of this study.